Idiopathic primary ovarian insufficiency is associated with anogenital distance, a marker for prenatal environment. (March 2021) - Dural, Ozlem; Kurbanova, Turkane; Yasa, Cenk; Ugurlucan, Funda Gungor; Selvi, Esra; Ozdemir, Pelin Kundakci; Akhan, Suleyman Engin
Abstract: Objective: In a significant number of women diagnosed with primary ovarian insufficiency ( POI), the underlying cause cannot be found. On the other hand, the ovarian reserve set prenatally has been shown to be affected by intrauterine nutrition, environmental and hormonal factors. We aimed to evaluate the relationship between anogenital distance (AGD), which is considered as a biomarker for prenatal hormonal environment, and idiopathic POI in adolescents and young women. Study design: This case control study was conducted between September 2018 and December 2019. The study group consisted of patients between the ages of 15–30, who developed POI following menarche without any identified genetic or iatrogenic cause. Controls were patients of the same age range who were having regular menstrual periods and were not diagnosed with polycystic ovary syndrome or endometriosis. Patients were excluded from the study if they were pregnant, had vaginal delivery or genital surgery. Distance between the anterior clitoral surface and the upper verge of the anus (AGDAC ), and between the posterior fourchette and the upper verge of the anus (AGDAF ) were measured in all subjects. Results: In total, 37 POI patients and 44 controls were included in the study. Two groups were similar for demographic parameters such as age and body mass index (BMI). Shorter AGDAC and AGDAF measurements were found to be associated with idiopathic POI. Conclusion: Our results provide the first evidence of a strong association between shorter AGD measurements and the presence of idiopathic POI suggesting that prenatal environment may have role in the development of POI.